Key Drivers of Sustainable Tourism Destination Attractiveness - Lefrand S. Pasuhuk; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The attractiveness of sustainable tourism destinations plays a crucial role in promoting responsible travel behaviors and supporting long-term destination development. This study aims to systematically identify and analyze the key determinants contributing to the attractiveness of sustainable tourism destinations. Employing a systematic literature review (SLR) methodology, this research analyzes peer-reviewed journal articles published between 2010 and 2024, retrieved from the Scopus database. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, a rigorous screening, data extraction, and synthesis process was conducted, resulting in a final sample of 126 relevant studies. The findings reveal six major factors influencing sustainable tourism destination attractiveness: tourist satisfaction, destination image and branding, crisis management, perceived quality and visitor experience, environmental and climate change concerns, and research, evaluation, and planning efforts. These insights offer practical implications for policymakers, tourism planners, and destination marketers seeking to enhance the competitiveness and sustainability of tourism destinations in a rapidly evolving global context.